The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1063/1.2189850
|View full text |Cite
|
Sign up to set email alerts
|

Re-entrant melting and freezing in a model system of charged colloids

Abstract: We studied the phase behavior of charged and sterically stabilized colloids using confocal microscopy in a low polarity solvent ͑dielectric constant 5.4͒. Upon increasing the colloid volume fraction we found a transition from a fluid to a body centered cubic crystal at 0.0415Ϯ0.0005, followed by reentrant melting at 0.1165Ϯ0.0015. A second crystal of different symmetry, random hexagonal close packed, was formed at a volume fraction around 0.5, similar to that of hard spheres. We attribute the intriguing phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
144
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(167 citation statements)
references
References 54 publications
21
144
2
Order By: Relevance
“…Instead, x-ray scattering studies [23] showed a fascinating phase behavior of Wigner crystals, including a body-centered-cubic (bcc) phase at low concentration, and a solid-solid transition to a face-centered-cubic (fcc) phase at higher densities [15][16][17][18]24,25]. It is also possible to induce charge on particles in nonaqueous solvents through the addition of charge control agents [21,[26][27][28]. However, in this case, there is strong coupling between the charge on the particle surface and the ions in solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, x-ray scattering studies [23] showed a fascinating phase behavior of Wigner crystals, including a body-centered-cubic (bcc) phase at low concentration, and a solid-solid transition to a face-centered-cubic (fcc) phase at higher densities [15][16][17][18]24,25]. It is also possible to induce charge on particles in nonaqueous solvents through the addition of charge control agents [21,[26][27][28]. However, in this case, there is strong coupling between the charge on the particle surface and the ions in solution.…”
mentioning
confidence: 99%
“…Typically, the colloids used for these studies are stericallystabilized polymeric particles in nonaqueous solvents, which can match both the density ρ and refractive index n of the particles, enabling confocal microscopy to be used for these investigations. Even earlier studies focused on charged particles, where crystallization is driven by strong long-range repulsive interactions arising from Coulombic charges on the particles [1,[10][11][12][13][14][15][16][17][18][19][20][21][22]. These studies were performed on particles in aqueous solvents, which makes charge effects much easier to induce, but precludes index matching, limiting the use of optical techniques except at very low densities.…”
mentioning
confidence: 99%
“…In the work by Royall et al, 6 a similar reentrant fluidbcc−fluid transition has been observed experimentally for charged PMMA spheres in a solvent mixture as the volume fraction was increased. The unusual part in this sequence is the reentrant melting at a larger φ. Royall et al explain this sequence essentially by the strong φ dependence of the effective colloid charge which, in the considered concentration range, decreases with an increasing φ.…”
Section: Discussionmentioning
confidence: 79%
“…Well-studied experimental systems which fall into this category are (sulfonate) polystyrene latex spheres in water 8,9 or in an ethanol-water mixture, 3,4 silica and polymethylacrylate (PMMA) spheres in an organic solvent (mixture), 6,10,11 and to some extent also charged globular proteins in water such as apoferritin 12,13 or bovine serum albumin (BSA). 14,15 The pair potential in Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation